Simulation and electromagnetic performance of cylindrical two-element microstrip antenna array integrated in 3D woven glass fiber/epoxy composites. (5th January 2016) - Xu, Fujun; Qiu, Yiping
Abstract: Three dimensional integrated microstrip antennas (3DIMA) can carry substantial external load while functioning as antennas. In this study, cylindrical two-element antennas integrated in three dimensional orthogonal woven glass fiber/epoxy composites with various curvatures are fabricated. The effects of the cylindrical curvature on the electromagnetic performance of the 3DIMAs are simulated using High Frequency Structural Simulator and verified experimentally. The results show that all cylindrical 3DIMAs, with different radii of curvature, namely 75, 60, and 45 mm, exhibit utility return losses of − 20 dB. However, their resonant frequencies and gains are significantly influenced by the curvature as well as the arrangement of the curvature and feeding directions. When the curvature of the cylindrical structure was along the feeding direction of the antenna, the 3DIMAs showed more stable resonant frequencies (around 1.5 GHz), gain values (from 2.37 dB to 1.44 dB) and proper radiation patterns, compared with the antenna with the curvature perpendicular to the feeding direction. Graphical abstract: Highlights: Two-element microstrip antennas were integrated into cylindrical 3D woven composites. The cylindrical 3DIMAs with the radii of 75, 60, 45 mm were demonstrated. Electromagnetic performance was simulated and matched well with the tested results. 3DIMAs-AFd was subjected lower negative impact under the curvature structures.